Effect of object substitution, spontaneous compensation and repetitive training on reaching movements in a patient with optic ataxia. Issue 9 (20th October 2020) - Baumard, Josselin; Etcharry-Bouyx, Frédérique; Chauviré, Valérie; Boussard, Delphine; Lesourd, Mathieu; Remigereau, Chrystelle; Rossetti, Yves; Osiurak, François; Le Gall, Didier
ABSTRACT: We report the case of M.B. who demonstrated severe optic ataxia with the right hand following stroke in the left hemisphere. The clinical picture may shed light on both the pathological characteristics of reaching and grasping actions, and potential rehabilitation strategies for optic ataxia. First, M.B. demonstrated a dissociation between severely impaired reaching and relatively spared grasping and tool use skills and knowledge, which confirms that grasping may be more intermingled with non-motoric cognitive mechanisms than reaching. Besides, M.B.'s reaching performance was sensitive to movement repetition. We observed a substitution effect: Reaching time decreased if M.B. repeatedly reached toward the same object but increased when object identity changed. This may imply that not only object localization but also object identity, is integrated into movement programming in reach-to-grasp tasks. Second, studying M.B.'s spontaneous compensation strategies ascertained that the mere repetition of reaching movements had a positive effect, to the point M.B. almost recovered to normal level after an intensive one-day repetitive training session. This case study seems to provide one of the first examples of optic ataxia rehabilitation. Reaching skills can be trained by repetitive training even two years post-stroke and despite the presence of visuo-imitative apraxia.